(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the therapeutic effects of the “Kien thong thang 103” combined with electroacupuncture and hydroacupuncture in patients with cervical shoulder arm syndrome due to cervical spondylosis. Methods: This is a prospective study, pre- and post-treatment comparison with control on 60 patients diagnosed with cervical shoulder arm syndrome due to cervical spondylosis. The patients were treated at the Department of Traditional Medicine, Military Hospital 103 from January 2024 to December 2024. Results: After 15 days of treatment, the study group showed significant improvements in VAS scores, cervical spine range of motion, and NDI scores compared to pre-treatment values (p < 0.05). The degree of improvement in these indicators was greater and statistically significant compared to the control group (p < 0.05). Conclusion: The “Kien thong thang 103” combined with electroacupuncture and hydroacupuncture demonstrated good therapeutic efficacy in patients with cervical shoulder arm syndrome due to cervical spondylosis.